Stability Guarantees for a Class of Networked Control Systems Subject to Stochastic Delays - Schlotterbeck, Constanza; Gallegos, Javier A.; Teel, Andrew R.; Nunez, Felipe (IEEE transactions on automatic control, 2024)
Stability guarantees in networked control systems (NCSs) have traditionally been addressed in the deterministic setting using the concepts of maximum allowable transmit interval and maximum allowable delay (MAD). Motivated by the widespread use of nondeterministic networks in modern industrial NCSs, this note aims to extend the analysis to the stochastic setting by considering a setup where the NCS faces stochastic communication delays, which take values over the MAD with positive probability. Conditions for uniform asymptotic stability in probability are given and their practical relevance is illustrated through a set of experiments performed on a real testbed.